"Once you join the streets you will have to do it": sexual practices of street children and youth in Uasin Gishu County, Kenya. Issue 1 (December 2015) - Embleton, Lonnie; Wachira, Juddy; Kamanda, Allan; Naanyu, Violet; Winston, Susanna; Ayuku, David; Braitstein, Paula
Abstract Background Adolescents living in HIV endemic settings face unique sexual health risks, and in the context of abject poverty, orphanhood, social marginalization, and discrimination, adolescents may be particularly at-risk of horizontal HIV transmission. Street-connected children and youth are a particularly vulnerable and marginalized population and therefore may be a key population at-risk. Methods We sought to describe the sexual behaviours of street-connected children and youth in order to comprehend their sexual practices and elucidate circumstances that put them at increased risk of contracting HIV utilizing qualitative methods from a sample of street-connected children and youth in Eldoret, Kenya. We recruited participants aged 11–24 years who had lived on the street for ≥ 3 months to participate in 25 in-depth interviews and 5 focus group discussions stratified by age and sex. Results In total we interviewed 65 street-connected children and youth; 69 % were male with a median age of 18 years (IQR: 14–20.5 years). Participants identified both acceptable and unacceptable sexual acts that occur on the streets between males and females, between males, and between females. We grouped reasons for having sex into four categories based on common themes: pleasure, procreation, transactional, and forced. Transactional sex and multiple concurrent partnerships were frequently described by participants. Rape was endemic to street life for girls. Conclusion These findings have important policy and programming implications, specifically for the government of Kenya's adolescent reproductive health policy, and highlight the need to target out-of-school youth. There is an urgent need for social protection to reduce transactional sex and interventions addressing the epidemic of sexual and gender-based violence.